1995
DOI: 10.1209/0295-5075/31/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in Interaction-Assisted Coherent Transport

Abstract: The pair localization length L2 of two interacting electrons in one-dimensional disordered systems is studied numerically. Using two direct approaches, we find L2 ∝ L α 1 , where L1 is the one-electron localization length and α ≈ 1.65. This demonstrates the enhancement effect proposed by Shepelyansky, but the value of α differs from previous estimates (α = 2) in the disorder range considered. We explain this discrepancy using a scaling picture recently introduced by Imry and taking into account a more accurate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
180
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(201 citation statements)
references
References 8 publications
18
180
3
Order By: Relevance
“…This conclusion was confirmed and extended to higher dimensions via Thouless block scaling picture by Imry [2]. The subsequent numerical studies [3,4,5,6,7,8,9,10] verified the main qualitative results concerning the presence of Shepelyansky states, mostly by supressing single particle transport via efficient Green function or bag model methods which examine pair propagation [8].The deviations from the predicted behavior of the two-particle localization length ξ found were usually attributed to the oversimplified statistical assumptions concerning the band random matrix model of the original Shepelyansky construction.However, there is an ongoing debate whether coherent pair propagation actually exists for two interacting electrons in infinite disordered systems [11,12], which began by a recent transfer matrix study where no propagation enhancement is found at E = 0 for an infinite chain [11]. Moreover, it was pointed out that the reduction to a SBRM relies on questionable assumptions regarding chaoticity of the non-interacting electron localized states within ξ 1 , so that the relevant matrix model could be prob-2 ably different [13,14].…”
supporting
confidence: 58%
“…This conclusion was confirmed and extended to higher dimensions via Thouless block scaling picture by Imry [2]. The subsequent numerical studies [3,4,5,6,7,8,9,10] verified the main qualitative results concerning the presence of Shepelyansky states, mostly by supressing single particle transport via efficient Green function or bag model methods which examine pair propagation [8].The deviations from the predicted behavior of the two-particle localization length ξ found were usually attributed to the oversimplified statistical assumptions concerning the band random matrix model of the original Shepelyansky construction.However, there is an ongoing debate whether coherent pair propagation actually exists for two interacting electrons in infinite disordered systems [11,12], which began by a recent transfer matrix study where no propagation enhancement is found at E = 0 for an infinite chain [11]. Moreover, it was pointed out that the reduction to a SBRM relies on questionable assumptions regarding chaoticity of the non-interacting electron localized states within ξ 1 , so that the relevant matrix model could be prob-2 ably different [13,14].…”
supporting
confidence: 58%
“…is the wave vector of slice n, H ⊥ is the SP hopping term for the second (m) particle (corresponding to the transverse direction) and (χ n ) i,m = [µ n + µ m + U n,m ]δ i,m codes the QP potential and the interaction [8]. Note that in this approach the symmetry of the wave function remains unspecified and we cannot distinguish between boson and fermion statistics.…”
Section: The Transfer-matrix Approach To Tipmentioning
confidence: 99%
“…(6) only N = M times will not give convergence. Frahm et al [8] have solved this problem in their TMM study by exploiting the Hermiticity of the product matrix…”
Section: The Transfer-matrix Approach To Tipmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is contrary to the localization of non-interacting particles in a onedimensional random potential, where the ground state wave function becomes localized for infinite small disorder strength. An ingeneous theoretical approach to the interplay of interactions and disorder is based on the twointeracting-particles (TIP) problem in one-dimensional random potential [8][9][10][11]. Furthermore, numerical results for spinless fermions in a random potential at finite particle density have given additional insight [12,13].…”
Section: Introductionmentioning
confidence: 99%